民間珍貴文書清查－以我國公營事業工會組織為例 - 黃紹恆 (My University, 2008)
檔案管理局自93年起，推動公營事業移轉民營檔案訪查徵集計畫，除了完成16家公營事業機構檔案訪查，並陸續完成中華電信股份有限公司等8家機構檔案移轉。因此，公營事業機構檔案已是檔案管理局現有重點館藏。然而，在這些質與量均可觀且珍貴的公營事業公務檔案之外，解嚴前後政治改革與社會運動的風起雲湧，各大公營事業工會紛紛從「御用工會」轉型為「自主工會」，甚至成為戰後台灣勞工運動的主力迄今，然而相關資料檔案卻未必完整地蒐羅到。換言之，檔案管理局所徵集之公營事業檔案，可以想見工會相關檔案，特別是目前依舊留存於民間的相關檔案，顯然仍有相當大的徵集必需及空間，同時也突顯出本研究計畫的必要性。 尤其是，公營事業工會分別因為隸屬機關不同、民營化時間方式不同，導致不同的性格與結局。因此，各大公營事業工會發展歷程的相關史料文件，適足以提供使用者及研究者對於各大公營事業多元面向的瞭解與認知。同時，對於檔案管理局相關檔案典藏的完整，亦有不可或缺之重要性。綜上所述，檔案管理局雖說已然典存可觀珍貴之公營事業公務檔案，如果能再積極徵集各大公營事業工會組織運作、活動紀錄相關史料文件之「民間珍貴文書」，一則豐富國家檔案內涵，再則俾利使用者與研究者得以互相參照觀點、對比立場。然而，此一全面性龐大徵集作業實非一蹴可幾，作為日後正式徵集典藏事業開展的前置準備作業，本研究計畫擬先清查目前現存之公營事業工會組織相關史料文件數量，以及探訪已解散工會組織之重要私人收藏文書現狀，希冀本研究計畫清查成果得以提供檔案管理局後續徵集公營事業工會組織私人文書作業時之參考依據。

The checking of private own precious documents-use our country’s government own labor union as example Summarize From year 2004, the division of document management started to push forward the project which is checking the private own enterprise documents that originally is government own documents. After completed checking 18 government own enterprises’ documents, and transferring the documents of 8 enterprises which also include “China telecom”. So, government own enterprise documents has already became documents of the division of document management which is very seriously taking care at the moment. However, besides those huge and good quality government own enterprises’ documents, as those government own enterprises started to change from “government own union” to “independent union” by government revolution and social activities, some even became the major force of Taiwan’s labor activities until now. In other words, some of relevant documents were not completely gathered up. It is important to push forward the project as there are still a lot of improving space of gathering those documents which is still left in the private own enterprise. Especially, government own enterprise unions will have different characteristics and results due to belong to different organization. So the relevant history documents that is about development of major government own enterprise unions can give the users and researchers to understand and realize the multiple faces of major government own enterprise. Meanwhile, it is important to complete the division of document management’s documents. However, the project will involve huge time in sourcing and gathering works, so for the preparation works of officially collecting documents, the research project will check the numbers of present government own enterprise unions’ relevant history documents and checking the important private owned documents which is about the unions that had already not activated now. We hope the project’s result will be able to be the references for division of document management when collecting government own enterprise union’s private own documents in the future.
The checking of private own precious documents-use our country’s government own labor union as example
Keywords: 民間珍貴文書清查; 公營事業工會; The checking of private own precious documents; government own enterprise unions